On ecocriticism and hispanism and on Francisco González Díaz, apostle of modernist trees - Marrero Henríquez, José Manuel (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
On ecocriticism and hispanism and on Francisco González Díaz, apostle of modernist trees